Longitudinal alterations of pulmonary V.O2 on-kinetics during moderate-intensity exercise in competitive youth cyclists are related to alterations in the balance between microvascular O2 distribution and muscular O2 utilization - Hovorka, Matthias; Prinz, Bernhard; Simon, Dieter; Zöger, Manfred; Rumpl, Clemens; Nimmerichter, Alfred (Frontiers in Sports and Active Living, 2022)
Purpose The main purpose of the current study was to investigate the dynamic adjustment of pulmonary oxygen uptake (V.O2) in response to moderate-intensity cycling on three occasions within 15 months in competitive youth cyclists. Furthermore, the muscle Δdeoxy[heme] on-kinetics and the Δdeoxy[heme]-to-V.O2 ratio were modeled to examine possible mechanistic basis regulating pulmonary V.O2 on-kinetics. Methods Eleven cyclists (initial age, 14.3 ± 1.6 y; peak V.O2, 62.2 ± 4.5 mL.min−1.kg−1) with a training history of 2–5 years and a training volume of 10 h per week participated in this investigation. V.O2 and Δdeoxy[heme] responses during workrate-transitions to moderate-intensity cycling were measured with breath-by-breath spirometry and near-infrared spectroscopy, respectively, and subsequently modeled with mono-exponential models to derive parameter estimates. Additionally, a normalized Δdeoxy[heme]-to-V.O2 ratio was calculated for each participant. One-way repeated-measures ANOVA was used to assess effects of time on the dependent variables of the responses. Results The V.O2 time constant remained unchanged between the first ( 24 s) and second visit ( 22 s, P > 0.05), whereas it was significantly improved through the third visit ( 13 s, P = 0.006–0.013). No significant effects of time were revealed for the parameter estimates of the Δdeoxy[heme] response (P > 0.05). A significant Δdeoxy[heme]-to-V.O2 ratio “overshoot” was evident on the first (1.09 ± 0.10, P = 0.006) and second (1.05 ± 0.09, P = 0.047), though not the third (0.97 ± 0.10, P > 0.05), occasion. These “overshoots” showed strong positive relationships with the V.O2 time constant during the first (r = 0.66, P = 0.028) and second visit (r = 0.76, P = 0.007). Further, strong positive relationships have been observed between the individual changes of the fundamental phase τp and the Δdeoxy[heme]-to-V.O2 ratio “overshoot” from occasion one to two (r = 0.70, P = 0.017), and two to three (r = 0.74, P = 0.009). Conclusion This suggests that improvements in muscle oxygen provision and utilization capacity both occurred, and each may have contributed to enhancing the dynamic adjustment of the oxidative “machinery” in competitive youth cyclists. Furthermore, it indicates a strong link between an oxygen maldistribution within the tissue of interrogation and the V.O2 time constant.